In vitro treatment of MCF-7 and MDA-MB-231 breast cancer cell lines with doxorubicin and vincristine sulphate calcium carbonate nanoparticles - Mengyi, Xue (2019)
Vincristine Sulphate (VCR) and Doxorubicin (DOX) are standard chemotherapy drugs widely used as a systemic treatment for cancer. As for most kinds of solid tumor, they can help achieve an acceptable anticancer activity respectively. The dose limiting side effects, narrow pharmaceutics index with unique pharmacological profile and multidrug resistance (MDR) largely limits the range of application. Breast cancer can be regarded as a public health issue which bears the highest rate of female malignant disease diagnose around the world. Thus, discovering a high-performance of anticancer drug delivery is important. In this study, cockle shell-derived calcium carbonate nanoparticles (ANPs) along with Vincristine Sulphate and Doxorubicin was synthesized as the passive targeting nanoparticles drug delivery system. The DOX/VCR-ANPs co-delivery system and VCR-ANPs delivery system were characterized and evaluated through TEM, FESEM, Zeta sizer and Zeta potential. Drug loading and control release study, MTT assay, cell uptake assay, cell morphology observation, and AO/PI double stain assay in vitro were also conducted. Through this study, the results revealed that the cockle shells-derived CaCO3 aragonite nanoparticles (ANPs) are homogeneous spherical and porous particles with zeta potential negatively charge of -34.5 mV, and with a zeta size of 157.8 nm in diameter. After loading with DOX/VCR or VCR alone, the nanoparticle porosity become unclear and size increased. The result also shows that the Vincristine Sulphate and Doxorubicin can effectively be loaded into calcium carbonate nanoparticles and keep a fast release at pH 4.8 and a sustained release at pH 7.2 up to 3 days. After being loaded into ANPs, VCR exhibits a better anticancer efficiency in breast cancer treatment while the IC50 value of VCR-ANPs is half of that in free VCR. The synergistic effect of VCR and DOX significantly improves the antineoplastic efficient in vitro, which demonstrates the lowest combination index (0.0433 at 48 hours of treatment and 0.08325 at 72 hours of treatment) under the DOX/VCR ratio of 3/1. For the cell morphology examination under microscope and florescence microscope, the cells showed an evident apoptosis in vitro. Overall, aragonite nanoparticles delivery system loaded with VCR and DOX can efficiently act against breast cancer with higher anticancer efficiency and significant synergistic effect which can be attribute to the ANPs control release ability and the unique physicochemical property of aragonite nanoparticles.